PENGAKUAN DAN PEMENUHAN HAK-HAK PENGANUT ALIRAN KEPERCAYAAN DI BIDANG ADMINISTRASI KEPENDUDUKAN - Nico Ardine Faadihilah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The State of Indonesia has a diversity of tribes and cultures, Religions that have been recognized currently there are 6 religions namely (Islam, Christianity, Buddhism, Confucianism, Catholicism and Hinduism) regardless of the 6 religions that have been recognized by the Indonesian state, there is a stream of belief which has existed in Indonesia for a long time, but adherents of a belief system have not been recognized by the Indonesian state regarding the fulfillment of their rights in a Population Administration, the most obvious example and many people who embrace a belief system are not fulfilled Regarding access to religious education at the school level which should be obtained by adherents of that belief system, if in the population document it is recorded that it must be affiliated with the official state religions, then access to religious education is in accordance with official state teachings. If religion is adjusted according to population records, religious beliefs are recorded, access to education about religious knowledge should adjust to the beliefs adhered to, not forced to get access to religious knowledge that is appropriate in official religions. So in this study the author will try to explain the legal basis regarding beliefs in the Constitutional Court decision No.97/PUU-XIV/2016 which explains that the position of beliefs and religions should be placed equally, this also applies to adherents of beliefs who have the right -the same rights as adherents of official state religions in the field of population administration